Ameliorating effects of okra (Abelmoschus esculentus) seed oil on hypercholesterolemia - KHAN,Moazzam Rafiq (2021)
Abstract Lifestyle associated disorders have always been a hazard for the advancement of chronic diseases. Therefore, use of natural dietary sources is proved to be safe for reducing the occurrence and management of chronic diseases. Okra along with its various parts has been used for the treatment of several diseases. The present study was done to examine the ameliorating effect of okra seed oil on hypercholesterolemic rats. Spargue Dawley Rats were randomly divided into five groups fed with selected experimental diets for a period of 30 days. After inducing hypercholesterolemia, the rats in treatment groups were fed with 6%, 12% and 18% okra seed oil respectively mixed with their normal diet. Decrease in cholesterol and LDL were observed in group 2, 3 and 4. Increase in HDL was also observed in group 2, 3 and 4 from 24.33 ± 1.29 to 25.33 ± 1.29, 23 ± 2.94 to 25 ± 2.94 and from 23.67 ± 1.29 to 26.67 ± 1.29 at day 28. A decrease pattern was also observed in triglycerides in group 2, 3 and 4 from 74 ± 2.22 to 72 ± 2.22, 72 ± 1.63 to 68 ± 1.63 and from 74 ± 3.11 to 66.67 ± 2.45 at day 28. Okra seed oil has the potential to ameliorate hypercholesterolemia. This vegetable can be a part of medical nutrition therapy.